The Prohibition of Demeaning Others in Surah Al-Hujurat Verse 11 A Study of Al-Baghawi's Interpretation - Roihana; Febrianti, Ines (Institut Agama Islam Persis Bandung, 2025)
The Prohibition of Demeaning Others in Surah Al-Hujurat Verse 11: A Study of Al-Baghawi's Interpretation] Surah al-Hujurāt verse 11 contains a prohibition against belittling others, which reflects the basic values ​​of Islamic social ethics. This study attempts to explore the meaning of this verse through an examination of al-Baghawi's Maʿālim al-Tanzīl, which represents the classical interpretation of the Sunni tradition. Using a qualitative approach and content analysis methods, this study examines the linguistic, theological, and social aspects surrounding this prohibition from al-Baghawi's perspective. The results of the analysis indicate that the acts of mocking, ridiculing, and giving demeaning titles are understood as violations of intersubjective ethics and threats to the moral order of the community. Al-Baghawi's interpretation emphasizes the importance of maintaining individual self-esteem and social stability through control over speech and attitudes. This finding confirms that the moral message in the verse remains relevant in building just and inclusive social relations, especially in the context of a pluralistic and dynamic society